Ответы и объяснения

2013-10-16T09:35:40+00:00
1 пример 2sin^2x +5cosx -4=0 2(1-cos^2x)+5cosx -4=0 -2cos^2x+5cosx-2=0 2cos^2x-5cosx+2=2 пусть cosx = а, то 2а^2-5а+2=0 Д=25-16=4 х1=4\3 х2=-1\3 если cosx = а, то cosx = -1\3                                     cosx =4\3 х=+-arccos(-1\3) + П,n ∈ z               х-нет реш.,тк. х∈[-1;1] ответ:х=+-arccos(-1\3) + П,n ∈ z
2013-10-16T09:47:10+00:00
Преобразуем выражение
 (sinx+cosx)^{2}= sin^{2}x+ cos^{2}x+2sinxcosx=1+sin2x    (sinx+cosx)^{2}=1+ \frac{3}{5}=1 \frac{3}{5}
Преобразуем второе выражение
5cos2x+ cos^{2}x=5( 2cos^{2}x-1 )+ cos^{2}x=11 cos^{2} x-5
5 cos^{2}2x+ cos^{2} x=11* \frac{2}{5} -5 =- \frac{3}{5}